Characteristics of pediatric traumatic brain injury: study from Wongsonegoro Regional Public Hospital in Semarang - Andrew Robert Diyo; Nadisa Tiofunda Budiman; Natashia Olivia Christian; Riky Pratama (Health Science Journal of Indonesia, 2021)
Background: Traumatic brain injury is one of the leading causes of morbidity and mortality in the world, as well as disability in the pediatric group. This study aimed to describe the characteristics of pediatric traumatic brain injury patients, considering the lack of data in Indonesia. Methods: We conducted a descriptive-retrospective study at Wongsonegoro Regional Public Hospital Semarang. Data were extracted from medical records of patients admitted during the period of January 2017-December 2019 using a purposive sampling method. Results: Out of 296 patients, most of the patients were male (59.13%; 66.30%). Based on age group, the highest percentage was found in the (11-18-year-old) (40.87%) in operative patients and 5-10-year-old (37.57%) in non-operative patients. The most common cause of traumatic brain injury in operative patients was falling from motor vehicle (37.39%) while in non-operative patients was falling while playing (32.60%). The most common type of injury in operative patients was epidural hematoma (49.57%) and in non-operative patients was brain concussion (53.59%). Most of the patients had minor head injury (75.65%; 81.22%). Most of operative patients spent 3-5 days (64.35%) in the hospital while most of non-operative patients spent 1-3 days (72.37%). Of all the subjects, the majority of patients recovered and discharged. Conclusion: remains as the most common type of pediatric traumatic brain injury in this study. This study provides an overview of traumatic brain injury in children and shows the importance of enforcing driving rules and supervision by parents which play an important role in child safety. Keywords: pediatric, traumatic brain injury, Indonesia Abstrak Latar belakang: Cedera kepala merupakan salah satu penyebab utama morbiditas dan mortalitas di dunia, serta disabilitas pada kelompok pediatri. Penelitian ini bertujuan untuk mendeskripsikan karakteristik pasien pediatri dengan cedera kepala, mengingat minimnya data cedera kepala pada anak di Indonesia. Metode: Penelitian ini merupakan penelitian deskriptif-retrospektif di RSUD Wongsonegoro Semarang. Data diambil dari rekam medis pasien anak yang dirawat selama periode Januari 2017-Desember 2019 dengan menggunakan metode purposive sampling. Hasil: Dari 296 pasien, sebagian besar merupakan laki-laki (59,13%; 66,30%). Berdasarkan kelompok umur, persentase tertinggi pada kelompok operatif terdapat pada (40,87%) dan pada kelompok non operatif terdapat pada kelompok usia 5-10 tahun (37,57%). Penyebab tersering cedera kepala pada pasien operatif yakni jatuh dari kendaraan bermotor (37,39%) sementara pada pasien non operatif penyebab tersering berupa jatuh saat bermain (32,60%). Jenis cedera kepala tersering pada pasien operatif adalah Epidural Hematoma (49,57%) dan pada pasien non-operatif berupa commotio cerebri (53,59%). Kebanyakan pasien mengalami cedera kepala ringan (75,65%; 81,22%). Sebagian besar pasien operatif dirawat selama 3-5 hari (64,35%) sedangkan mayoritas pasien non operatif dirawat selama 1-3 hari (72.37%) Dari semua subjek, mayoritas pasien sembuh dan dipulangkan. Kesimpulan: Jatuh dari kendaraan bermotor merupakan jenis cedera kepala yang paling umum ditemukan dalam penelitian ini. Studi ini memberikan gambaran umum tentang cedera kepala pada anak dan menunjukkan pentingnya penegakan aturan dalam berkendara serta pengawasan oleh orang tua yang berperan penting dalam keselamatan anak. Kata kunci: anak, cedera kepala, Indonesia